2017
DOI: 10.1039/c6pp00336b
|View full text |Cite
|
Sign up to set email alerts
|

The health benefits of UV radiation exposure through vitamin D production or non-vitamin D pathways. Blood pressure and cardiovascular disease

Abstract: The detrimental effects of ultraviolet radiation are well known. Skin cancer, photo-aging, and induction or exacerbation of photosensitive dermatoses have been the focus of most photobiological research since 1928 when Findlay confirmed the carcinogenicity of ultraviolet radiation using a murine model of skin cancer. The epidemiological, mechanistic and clinical trial data have enabled the classification by the International Agency for Research on Cancer of ultraviolet radiation as a Group 1 ('sufficient evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 60 publications
0
39
0
1
Order By: Relevance
“…More recently, there has been a growing appreciation for the beneficial impact that sunlight has on the cardiovascular system, independent of vitamin D production. Vitamin D could in these circumstances act as a marker for sunlight exposure and its postulated beneficial effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been a growing appreciation for the beneficial impact that sunlight has on the cardiovascular system, independent of vitamin D production. Vitamin D could in these circumstances act as a marker for sunlight exposure and its postulated beneficial effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that too much exposure is damaging to the skin and eyes and increases the risk of skin cancers [16][17][18][19][20]. However, exposure to solar UV-B benefits vitamin D production and bone health [21,22]; there is emerging evidence of the role of UV-A in cardiovascular health [15,18,[23][24][25][26][27][28][29][30][31][32], and there are suggestions that solar UV exposure reduces the risk of some cancers and other causes of death [18,[33][34][35]. In addition, solar radiation exposure as a whole, through exposure to visible radiation (400-700 nm), plays an important role in melatonin regulation for better quality sleep and serotonin regulation for improved mental health-both of which may enhance length and quality of life [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when we analyzed the most recent exposure, we observed that the magnitude of the effect was stronger, but these results were not statistically signi cant probably due to small sample size. Recent evidence suggests sun exposure might have a protective role in cardiovascular disease explained by the mobilization of nitric oxide skin stores to systemic circulation, which reduces systolic blood pressure (35). In agreement with this, observational studies have shown a reduction in blood pressure in participants who were more sunexposed, but these changes were not signi cant after adjusting for potential confounders (28).…”
Section: Discussionmentioning
confidence: 82%